Single dose (400mg) versus 7 day (200mg) daily dose itraconazole in the treatment of tinea versicolor: a randomized clinical trial - Wahab, MA; Ali, ME; Rahman, MH; Chowdhury, SA; Monamie, NS; Sultana, N; Khondoker, L (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):72-76. The abstract of this article is available on the PubMed website